THE ISLAMIC COMMUNITY IN CONTEMPORARY VIETNAM: MAIN FEATURES AND CURRENT ISSUES - Hoàng Van Chung; Chu Văn Tuấn (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2022)
It is believed that Islam was first introduced to the Chăm community around the eleventh century. Despite vicissitudes of the Champa kingdom’s history, this religion has remained and thrived in Vietnam until today. Specifically, Islam can only be found in a part of the Chăm – an ethnic of minority. Currently, the population of the Islamic community has reached about 40,000 and been distributed unevenly in 12 provinces and cities from the Central region to the Southern region. Based on the analysis of data gathered from survey and fieldworks conducted during 2019-2020 across the country where the Muslim Chăm community present, this article presents an overview of the Islamic community in contemporary Vietnam. Main features generalized and analyzed here includes population, distribution, and relationships of the Muslim community with the broader society and with international partners. It also identifies emerging problems putting forwards for this community at the present. We would argue that recent and notable changes of the Muslim community have revealed its efforts of adaptation toward the current social context characterized by modernity, secularization, urbanization and world integration.